ISOLASI DAN AKTIVITAS LARVACIDA MINYAK ATSIRI AKAR (Curcuma mangga, Val.) TERHADAP LARVA Aedes Aegypti DAN PROFIL GC-MS NYA - Lolita, Lolita (Pharmaciana, 2012)
Curcuma mangga, Val. has been recognized as a traditional drug since a longtime ago. The active ingrediences of this plant especially the volatile oil containsmonoterpenes and sesquiterpenes. This research was aimed to study about thelarvacideâs activity of the volatile oil Curcuma mangga, Val. rhizome and also toanalyze its chemical compounds using the GC-MS. The volatile oil was isolated fromCurcuma mangga, Val. with steam and water distillation. The test method for larvicidewas done by dissolving the substances into water and added by Tween 20 10% v/v to thethe volatile oil. The concentration of the volatile oil of Curcuma mangga, Val. rhizomewere 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, and 350 ppm. The concentrationof positive control âabateâ were 0,01 ppm; 0,025 ppm; 0,05 ppm; 0,1 ppm; 0,5 ppmwhile as the negative control was Tween 20 solution. The perception time of larvaeâsmortality was 24 hours. The chemical compound of Curcuma mangga, Val. can beanalysed by the GC-MS. Data of larvaeâs mortality were used to estimate the values ofLC50 with the probit analyzis method. This study showed that the volatile oil of Curcumamangga, Val. have clear-brass colour, bitter taste, typically aromatic like mango,rendement equal to (1,23 Â± 0,029)% v/b and refractive index 1,4881. The value of LC50for the volatile oil of Curcuma mangga, Val. rhizome is (216,17 Â±12,51) ppm whileabate equal to (0,072 Â± 0,024) ppm. This finding indicates that abate were more potentto larvae of Aedes aegypti. The GC-MS showes 30 peaks chromatogram and six peakswhich indicates the possibility of alpha-pinene, camphene, beta-pinene, beta-myrcene,eukalyptole, ar-turmerone presence.